2014
DOI: 10.5424/sjar/2014123-5327
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the potential of solar energy in pressurized irrigation networks. The case of Bembézar MI irrigation district (Spain)

Abstract: IntroductionIn the interest of sustainable development and the minimization of climate change impacts, national and international policies are prioritizing the improvement in the use of the natural resources. Water is an essential and limiting resource for private use, industry and agriculture that requires large amounts of energy for AbstractThe high energy requirements and the rising costs highlight the need to reduce the energy dependence of the irrigation sector. Alternative management strategies have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 29 publications
0
8
0
2
Order By: Relevance
“…However, optimal management of irrigation networks does not avoid the dependence of irrigation agriculture on fluctuations in energy prices. Therefore, in recent years, the reduction of electricity production costs from renewable energy sources (wind, solar photovoltaic and micro hydropower) is facilitating their incorporation into the irrigation sector [64,95,96]. Since the generation of energy depends on suitable weather conditions (sufficient wind or solar radiation for pumping), irrigation must be scheduled around the availability of renewably sourced energy [64].…”
Section: • Weather Datamentioning
confidence: 99%
“…However, optimal management of irrigation networks does not avoid the dependence of irrigation agriculture on fluctuations in energy prices. Therefore, in recent years, the reduction of electricity production costs from renewable energy sources (wind, solar photovoltaic and micro hydropower) is facilitating their incorporation into the irrigation sector [64,95,96]. Since the generation of energy depends on suitable weather conditions (sufficient wind or solar radiation for pumping), irrigation must be scheduled around the availability of renewably sourced energy [64].…”
Section: • Weather Datamentioning
confidence: 99%
“…On-farm-energy solar generation has proven to be a suitable alternative to reduce energy costs in irrigation. For instance, Carrillo-Cobo et al [89] estimated a reduction in energy costs of 60% in the Bembézar MI irrigation district (Andalusia) driven by the implementation of photovoltaic energy. Additionally, the recent change in energy legislation (i.e., the Royal Decree 244/2019, 5 April, that specifies the arrangements for administrative, technical and economic conditions for electric energy self-consumption), which eliminates taxes to electric energy self-consumption in Spain, might boost the expansion of solar energy in agriculture, with implications for irrigation costs that will need to be further assessed under tailored water cost scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…Carrillo-Cobo et al [55] evaluating the potential of solar energy in pressurized irrigation, with a case study in the district of Bembézar MI (Spain), developed a new methodology that combined sectorization as a measure of energy and solar energy saving, thus reducing energy requirements and dependence on conventional energy resources. The results showed that this measure could reduce the annual energy bill by 30.4% without large investments.…”
Section: Solar Pv Pumping Systemmentioning
confidence: 99%